EUTHANASIA AND MORAL DILEMMAS - Arsić, Miloš (Medicinski časopis, 2022)
The permissibility of the practice of voluntarily ending the life of a seriously ill person, in order to deprive him of further pain and suffering, is the subject of numerous and heated debates. Attitudes on this complex issue, to put it mildly, are not unanimous. While on the one hand, the supporters of euthanasia affirmatively speak about the act in question and advocate for its legalization, its opponents, presenting it as a negation of basic human rights, the right to life, tend to make meaningless any positive effect it could bring. In the shadow of the relationship between the right to life and the right to decide on death, is the controversy about the justification of euthanasia from the legal aspect, there is a moral segment of this act, which must not be neglected. In this regard, the question arises, whether it is moral to decide on the end of one’s own life, first of all, having in mind the fact that no one participated in making the decision to start it. The issue of the influence of the circumstances of a specific case, the type of disease, the intensity of pain and suffering to which the person is exposed, on the moral assessment of making or executing the decision to end life is also important. The main task of the theoretical treatment is to get acquainted with the basic features of the act of euthanasia, its perception through the prism of moral norms, both from the point of view of the person who decides to end his own life and from the point of view of the doctor who implements the decision. The choice of the subject of this theoretical treatment is encouraged, above all, by its practical significance, as well as the need for constant moral re-examination of one’s own actions, especially in the context of the serious crisis of the value system that characterizes the modern era.